Investigation of the effectiveness of antimicrobial photocatalyst-coated hand-contact surfaces in passenger transport vehicles under everyday conditions - Eicker, Rudolf; Salomon, Wilhelm (International Journal of Infection Control, 2021)
The coronavirus disease-2019 pandemic affects all aspects of public life. Measures for infection prevention are implemented in various sectors, in businesses, as well as in private life. Public transport is important and indispensable in daily life for both children and adults. Public transport companies have to take necessary actions to protect passengers and drivers from infections. Skin contact is one of the ways of transmitting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This research study was designed to evaluate the effectiveness of a photocatalytic, antimicrobial active surface coating under everyday – not hospital – conditions. To date, such coatings have been used in hospitals as an additional measure to regular cleaning and disinfection in order to reduce the risk of infection. We collected samples for bacterial cultures in three classes of public transport vehicles: bus, underground, and tram. Seven different hand-contact surfaces in one vehicle of each class were coated, while the other vehicles remained uncoated. All vehicles were in regular use. The number of colony-forming bacterial units per cm2 (CFUs/cm2) was measured. A representative number of isolates were differentiated at the pathogen level. Data collected were entered into GraphPad Prism (GraphPad Software, San Diego, USA) and analyzed. Overall, no statistically significant reduction in the number of colony-forming units (CFUs) was observed for coated versus uncoated surfaces. Samples with a very high colony count (>250 CFU/25 cm2) were equally distributed in both groups, coated and uncoated vehicles. Within one vehicle type, there was no significant difference between the coated and the uncoated vehicle. No relevant infection-preventive effect could be proven.